Assessing Children’s Executive Function: BADS-C Validity - Fish, Jessica; Wilson, F. Colin (Frontiers in Psychology, 2021)
Objectives. To investigate the external and ecological validity of a standardised test of children’s executive functioning, the Behavioural Assessment of the Dysexecutive Syndrome for Children (BADS-C). Background. There are few standardised measures for assessing executive functions in children, and the evidence for the validity of most measures is currently limited. Method. A normative sample of 256 children from age 8-16 completed the BADS-C, and a parent or teacher completed rating scales of the child’s everyday problems related to executive functioning (Children’s version of the Dysexecutive Questionnaire; DEX-C) and (Strengths and Difficulties Questionnaire, SDQ), a commonly used measure concerning emotional, social, cognitive and behavioural problems. Key Findings. Exploratory factor analyses yielded a two-factor structure to the BADS, indicative of monitoring and abstract reasoning processes, and a three-factor structure to the DEX-C, reflecting behavioural and cognitive components of the dysexecutive syndrome as well as emotional responsiveness. Regression analyses showed significant relationships between BADS-C scores and everyday functioning as reported on the DEX and SDQ. Furthermore, there were significant differences in BADS-C scores between those children in the upper and lower quartiles on the SDQ. Conclusions. Results provide tentative evidence of BADS-C and DEX-C convergent and predictive validity.